Tactics of Surgical Repair of Single Ventricle with Excessive Pulmonary Blood Flow and Obstruction of the Distal Arch of the Aorta in Newborns - Roman J. Lekan; Ivan R. Lekan; Oleksandr V. Popsuiko (Ukrainian Journal of Cardiovascular Surgery, 2024)
Pulmonary artery stenosis with distal aortic arch reconstruction and coarctation of the aorta in newborns is an effective palliative procedure for single ventricle and high pulmonary hypertension on the way to total cavo-pulmonary anastomosis.The aim. To present a case of complex correction of a single ventricle of the heart with tricuspid valve atresia and high pulmonary hypertension, obstruction of the distal aortic arch and coarctation of the aorta, and a final effective Fontan procedure with a good long-term outcome.Case report. On December 15, 2011, a 9-day-old newborn patient M. was admitted for treatment at the Department of Cardiovascular Surgery of Odesa Regional Children’s Clinical Hospital with a diagnosis of: a single ventricle of the heart, transposition of the great arteries, tricuspid atresia, distal arch hypoplasia, coarctation of the aorta, patent ductus arteriosus, high pulmonary hypertension. The first stage of surgical treatment was carried out on December 19, 2011: main pulmonary artery banding, reconstruction of the distal arch of the aorta through modified Amato technique, closure of the patent ductus arteriosus, resection of the coarctation of the aorta and extended end-to-end aortoplasty. At the age of 1 year (December 27, 2012), the second stage was performed: bidirectional Glenn procedure with plastic surgery of bifurcation and right pulmonary artery branch. The third stage was performed at the age of 3 years 11 months (November 19, 2015): Fontan procedure with extracardiac conduit.Conclusions. Early elimination of pulmonary hypertension by pulmonary artery banding ensures the preservation of the pulmonary vascular bed with low resistance, which is a crucial condition for the effective final hemodynamic correction of the single ventricle of the heart – the Fontan procedure. In case of hypoplasia of the distal aortic arch with coarctation in newborns, one of the alternative approaches is the use of modified Amato technique avoiding artificial circulation.